2020
DOI: 10.1111/jfpe.13499
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of tannase enzyme for degradation of tannin from cashew apple juice: Modeling and optimization of process using artificial neural network and response surface methodology

Abstract: The study was conducted on tannase-assisted extraction of cashew apple juice at different combinations of tannase concentration (0.01-0.1% wt/wt), incubation time (20-120 min), and incubation temperature (30-50 C) for the maximum reduction of tannin from the juice. The modeling and optimization of process parameters were performed using response surface methodology (RSM) and artificial neural network (ANN). The RSM proposed an optimum process condition of 0.079% tannase concentration, 85 min incubation time, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 33 publications
2
26
0
1
Order By: Relevance
“…Due to the free radical scavenging capacity, the phenolic compounds like flavonoids and tannins are denoted as the main group of antioxidant phytochemicals with remarkable properties. 31 The results supports the findings of Abdullah et al 29 and Jana et al 7 that the tannase treated fruit juices showed 78.44 % and 87.7 % of DPPH radical scavenging activity respectively.…”
Section: Antiradical Scavenging Assaysupporting
confidence: 81%
“…Due to the free radical scavenging capacity, the phenolic compounds like flavonoids and tannins are denoted as the main group of antioxidant phytochemicals with remarkable properties. 31 The results supports the findings of Abdullah et al 29 and Jana et al 7 that the tannase treated fruit juices showed 78.44 % and 87.7 % of DPPH radical scavenging activity respectively.…”
Section: Antiradical Scavenging Assaysupporting
confidence: 81%
“…The fresh and ripened cashew apples were collected and packed in polythene bags from the farm near Chatrapur, Odisha, India, and transported to the National Institute of Technology, Rourkela, Odisha. The juice was extracted, and bagasse was separated according to the method explained by Abdullah, Pradhan, Aflah, & Mishra (2020). The bagasse was then dried at 50 C for 24 hr in a hot air oven for moisture removal (Romanini et al, 2021).…”
Section: Collection Of Raw Materialsmentioning
confidence: 99%
“…Gallic acid (3,4, 5-tri hydroxyl benzoic acid) is an intermediate to produce the antifolic antibacterial drug, trimethoprim and has the potential to treat breast and cervical cancer [10]- [13]. Another industrial tannase application is a clarifying agent to clarify grape juice, tea, coffee, coffee-flavored soft drink, and detannification of effluents from the leather industry [14], [15]. Recent studies showed that bacterial and fungal strain capable of synthesizing tannase mostly from the genus Aspergillus spp., Penicillium,spp.…”
Section: Introductionmentioning
confidence: 99%
“…and Bacillus spp. [1], [13]- [15], [18] Submerged fermentation (SmF) is a fermentation process where microorganisms grow in liquid broth with excess water, while solid-state fermentation (SSF) is a fermentation process with a very low amount of free water present in the substrate, just sufficient to support microorganism growth [17], [19]. SmF was performed in this study due to several advantages over SSF regarding ease to sterile, fully utilizing substrate media, shorter incubation time, and ease for extracellular enzyme recovery [9], [13].…”
Section: Introductionmentioning
confidence: 99%